Service Failure and Recovery: The Best Defense Is a Good Attack - Dewi Wuisan; Hendra Achmadi; Oscar Jayanagara; Sylvia Samuel; Gracia Shinta S. Ugut (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Service failure is an inevitable aspect of any service-oriented business. When failures occur, the organization’s response is critical in shaping customer perceptions, satisfaction, and loyalty. This paper explores the notion that "the best defense is a good attack" in the context of service failure and recovery strategies. Proactive recovery initiatives, such as clear communication, swift actions, and personalized solutions, often outperform reactive or passive approaches in mitigating the negative effects of service failures. By employing a strategic recovery process, businesses not only address the immediate dissatisfaction but also create opportunities to strengthen customer relationships and even enhance brand reputation. The study examines key components of successful service recovery, including the role of empathy, transparency, and empowerment of frontline employees. It highlights the importance of preemptive measures such as employee training and the establishment of service recovery protocols. Furthermore, this paper discusses the psychological impact of recovery efforts on customers, emphasizing the significance of perceived justice—distributive, procedural, and interactional. Drawing from real-world examples and empirical studies, this research provides actionable insights for managers aiming to transform service failures into opportunities for improvement and differentiation. By adopting a mindset of proactive engagement, businesses can turn potentially negative experiences into moments that foster customer trust and loyalty. Ultimately, the findings suggest that an offensive approach in service recovery is not merely damage control but a strategic advantage in the competitive service landscape.